Sosialisasi Mitigasi Bencana Gempa Bumi dan Simulasi Teknologi Internet of Things (IoT) di Sekolah Madrasah Aliyah Negeri 1 Maluku Tengah - Rachman, Gazali; Manuhutu, Fredrik; Jamaludin; Batlolona, John Rafafy; Nurmin; Risahondua, Hatasudji (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The problem in Maluku is about earthquake mitigation and the lack of our young generation or students who master Internet of Things (IoT) technology. The reason why this issue should be a major concern is because Maluku is an earthquake-prone area. Providing understanding about earthquakes and earthquake mitigation is carried out through outreach to schools so that it is hoped that teachers and students will become pioneers who can provide understanding or knowledge about earthquakes and earthquake mitigation for each family and in their respective environments. Apart from that, mastery of IoT technology is very important. This is because IoT is the basis for creating the industrial era 4.0. The lack of knowledge about IoT technology among students in Maluku is a concern in increasing students' knowledge about IoT technology. To overcome this problem, socialization and simulation activities were carried out in schools which were partners in the Community Service Program activities in providing IoT training and the application of IoT in the industrial world. It is hoped that mastering the basic knowledge of IoT technology can support innovative IoT-based learning processes. IoT-based learning provides stimulus for students to carry out various experiments that are more innovative, creative and independent. Earthquake mitigation socialization activities and IoT technology workshop activities will be carried out at MAN 1 School, Central Maluku.